FORMULASI DAN UJI STABILITAS SEDIAAN KOSMETIK PERONA PIPI (BLUSH ON) DARI EKSTRAK KULIT BUAH RAMBUTAN ( Nephelium lappaceum L) SEBAGAI COLORING AGENT - Ika Ayu Mentari; Rahmatang (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Blush On is one type of cosmetic that produces color on the cheeks, there are two types of dyes commonly used in cosmetics, namely natural dyes derived from plants and synthetic dyes derived from a mixture of two or more chemical compounds. Plants that are often used to form natural dyes are rambutan fruit skin which has anthocyanin content that can provide color pigments. This study aims to determine the extract of rambutan fruit skin can be formulated into a blush on preparation and to determine the stability of the blush on preparation. The research method was carried out experimentally including the extraction of rambutan fruit skin by the maceration method using 96% ethanol, making blush on preparations with three different concentrations including 10%, 20%, 30%. Checking the physical quality of blush on includes organoleptic testing, stability, preference, pH, irritation, spreadability and homogeneity. The results of the study showed that blush on preparations with a concentration of 10% produced a white color, a concentration of 20% was brown and a concentration of 30% produced a reddish brown color. This happens because there are different concentration levels of each formulation of active substances from rambutan fruit skin extract. The stability of the preparation after 3 weeks of storage showed stable results. The conclusion of this study is that rambutan peel extract can be used as a coloring agent in blush on preparations.